Bimbingan Kelompok Menggunakan Teknik Latihan Asertif Meningkatkan Keterampilan Komunikasi Interpersonal Siswa - Fadhila, Liqa; Riska Ahmad; Neviyarni; Rezki Hariko (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Limitations in interpersonal communication can hinder students' social development and affect students' ability to build healthy relationships, but many adolescents still lack interpersonal communication skills. This study aims to analyze the effect of group guidance using assertive training techniques in improving students' interpersonal communication skills. The type of research is experimental research with a non-equivalent Control Group Design. The study population amounted to 362 students. The sample of this study was 33 students. The methods used to collect data are interviews, questionnaires, and observations. The instrument used to collect data is a questionnaire sheet. The technique used to analyze data is inferential statistical analysis. The results showed that the control group's interpersonal communication skills score increased from 166.1 to 167.1, while the average score of the experimental group students' interpersonal communication skills increased. The results of hypothesis testing show differences in interpersonal communication skills in both groups. It is concluded that the assertive training technique effectively improves the interpersonal communication skills of grade students at the junior high school level.